PERANCANGAN DAN IMPLEMENTASI ALAT PEMBACA REGISTER kWh-METER SECARA OTOMATIS MENGGUNAKAN SHORT MESSAGE SERVICE PADA JARINGAN SELULER - Thomas, Thomas; Mardjoko, Pono Budi; Aripin, Joni (Universitas Tarumanagara, 2006)
Scheme of Appliance of reader of register kWh-meter automatically use the Short Message Service (SMS) at network cellular function to give the amenity to Perusahaan Listrik Negara (PLN) to note the level of usage electric power at customer.